Comparison Between SMMR and SSM/I Passive Microwave Data Collected Over the Antarctic Ice Sheet - Jezek, K. C.; Merry, C.; Cavalieri, D.; Grace, S.; Bedner, J.; Wilson, D.; Lampkin, D. (Byrd Polar Research Center, The Ohio State University, 1991)
Passive microwave brightness temperature data collected during the overlap period betwen the Scanning Multichannel Microwave Radiometer and the Special Sensor Microwave Imager are compared. Only data collected over the Antarctic Ice Sheet are used in order to limit spatial and temporal complications associated with the open ocean and sea ice. Linear regressions are computed from scatter plots of complementary pairs of channels from each sensor revealing hightly correlated data sets. That a simple linear model can be used to correlate the data is used to support the argument that there are important relative calibration differences between the two instruments.